Detection of Salmonella typhimurium using an electrochemical immunosensor. - Salam, Faridah; Tothill, Ibtisam E. (Elsevier Science B.V., Amsterdam., 2009)
An electrochemical immunosensor based on screen-printed gold working electrode with onboard carbon counter and silver–silver chloride pseudo-reference electrode for Salmonella typhimurium detection is described in this paper. Monoclonal anti-S. typhimurium antibody was immobilized using physical and covalent immobilization via amine coupling of carboxymethyldextran on the surface of the gold working electrode. A direct sandwich enzyme-linked immunosorbent assays (ELISA) format was then developed and optimized using a polyclonal anti-Salmonella antibodies conjugated to horseradish peroxidase (HRP) as the enzyme label. 3,3′,5,5′-Tetramethylbenzidine dihydrochloride (TMB)/H2O2 was used as the enzyme mediator/substrate system. Electrochemical detection was conducted using chronoamperometry at −200 mV vs. onboard screen-printed Ag–AgCl pseudo-reference electrode. The applied potential was selected through the study of the electrochemical behaviour of bare gold electrode with TMB–H2O2–IgG–HRP system. S. typhimurium detection of 5 × 103 cells ml−1 and 20 cells ml−1 was achieved respectively for physical and covalent antibody immobilization. The developed sensor was then compared to a commercial ELISA kit and a chromogenic agar plating method for meat samples analysis. The sensor format shows a promising technology for simple and sensitive detection system for Salmonella contamination. Rapid detection of Salmonella is a key to the prevention and identification of problems related
Keywords: Immunosensor; Screen-printed gold electrode; Salmonella; Electrochemical detection; Food monitoring